Dodging the scalpel-migration of intraventricular neurocysticercus cyst occurring during surgery - Chandra, Tripti; Verma, Ashish; Mohan, Suyash; Kumar, Raj; Jaiswal, Awdhesh; Kumar, Sunil (Journal of Pediatric Neurology, 2007)
The authors describe a case of a 12-year-old female with an intra-ventricular cysticercal cyst in the third ventricle, which migrated to left occipital horn during surgical evacuation. The present case highlights the utility of magnetic resonance imaging over computed tomography and role of early postoperative magnetic resonance imaging to rule out the possibility of cyst migration and treatment failure.
Keywords: Intraventricular neurocysticercosis; magnetic resonance imaging; migration